SYSTEM MANIFESTATIONS OF THE PERSONAL PROPERTIES OF THE LANGUAGE IN LOANS - Krupych, Sofia Olegovna (Psychological Prospects Journal, 2013)
The article presents the results of the theoretical analysis of systematic studies of domestic and foreign scientists on the problem of manifestation of speech in personality characteristics of the speaker.